MODERN METHODS AND ESSENCE OF ENSURING INFORMATION SECURITY IN THE INFORMATION SOCIETY - qizi, Toshboyeva Feruza To'lqin; Hamidovna, Bebutova Zulayxo (Antis Publisher, 2024)
In today's information society, the problem of information security is extremely important. In this article, the concept of information security and its tasks, threats to information security, the concept of encryption and types of encryptions, encryption standards, cryptography goals are given in-depth information. Issues of reliable protection of information were studied